Prosesi Mappaturru Sayyang Sebagai Media Penghubung dalam Pertunjukan Sayyang Pattudu di Mandar Sulawesi Barat - Heriyati Yatim; Andi Jamilah; Syakhruni Syakhruni (Seminar Nasional LP2M UNM, 2022)
Abstract. Sayyang Patuddu is a dancing horse in the form of performing arts carried out at certain moments in the procession of completing the completion of reading the Qur'an, weddings, commemorating the birthday of the Prophet Muhammad SAW, this show originates from Polewali Mandar, West Sulawesi. This show has been known since the 16th century during the reign of King IV of the Balanipa kingdom, namely Mara'dia Kanna Pattang Daengta Tommuane. At first a Sufi Named KH. Muhammad Thahir was known as Imam Lapeo (1838–1952). It is said that when Imam Lapeo went to Mecca he was inspired by several camels that were paraded around, around Jabal Rahmah, this inspired him so he trained a horse and became a means of motivating children in the Polewali area. Mandar asked that after completing the Qur'an he would be invited to ride a horse and be paraded around the village as a sign that the child was proficient at reading the Qur'an, this has become a cultural tradition in the Polewali Mandar area. The owner of Sayyang Patuddu did many things so that the performance in the community could be carried out properly, including diligently training his horse every night after washing it since the afternoon and resting it in the stable. This process is not easy, but the coaches are trying to make an intensive approach to create harmony and synergy between them. With a stick as a teaching aid, horses can be trained to lift their legs while nodding and shaking their heads. During performances, it is customary to listen to tambourine music (Qasidahan/Salawatan) as an accompaniment to Sayyang Patuddu at every performance. Keywords: Sayyang, Pattudu, Performance